Prevalence of Hepatitis C Virus Infection in a Surgical Population of Southeast China: A Large-Scale Multicenter Study - Ping Chen; Yang Zheng; Yubo Cai; Pengfei Zou; Nan Li; Conggao Peng; Hainv Gao; Jimin Liu; Yongping Chen; Zhaowei Tong; Lanjuan Li (Canadian Journal of Gastroenterology and Hepatology)
Background. Chronic HCV infection affects 80 million people globally and may progress to advanced liver disease. The present study aims to investigate the present epidemiology of HCV infection in a southeastern Chinese surgical patient cohort. Methods. Blood samples obtained from 78,484 surgical patients from 18 different city and county hospitals were enrolled. The incidence of serum HCV antibody positivity, HCV RNA load, and HCV genotyping, as well as demographics and relevant clinical history, were investigated. Data were stratified using the multistage cluster random sampling method and further analyzed using the SPSS-20 package. Results. HCV antibody positivity was detected in 0.15% of the population (95% confidence interval (CI): 0.12%–0.18%). Genotype 1b (55.74%) was the dominant type. The HCV infection peaked in the age groups of 16–20, 41–50, and 61–65 years, and it was higher in males than in females (0.19% vs. 0.13%, P<0.05). The geographical distribution of infection rates differed: 0.19% (95% CI: 0.14%–0.24%), 0.18% (95% CI: 0.13%–0.23%), and 0.06% (95% CI: 0.03–0.09%) in plain areas, islands, and valley regions, respectively. Patients with transfusion history and urban residence were associated with high HCV RNA levels (adjusted odds ratio = 11.24 and 6.20, P<0.05). Conclusion. The prevalence of HCV infection in this cohort from southeast China was 0.17%, which is lower than the reported 0.43% infection rate in China in 2006. This result can be (partially) explained by the improvement of blood donor screening and the successful campaign for the use of disposable syringes and needles.